2014
DOI: 10.1186/2049-6958-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing disorders in tracheostomised patients: a multidisciplinary/multiprofessional approach in decannulation protocols

Abstract: Safe removal of tracheal cannula is a major goal in the rehabilitation of tracheostomised patients to achieve progressive independence from mechanical support and reduce the risk of respiratory complications. A tracheal cannula may also cause significant discomfort to the patient, making verbal communication difficult. Particularly when cuffed, tracheal cannula reduces the normal movement of the larynx which can further compromise the basic swallowing defect. A close connection between respiratory, phonating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 50 publications
0
55
0
11
Order By: Relevance
“…In other words, when considering dysphagia, interventions by a multidisciplinary team including doctors, nurses, SLPs, physical therapists, nutritionists and dental hygienists are necessary. The importance of multidisciplinary teams for the treatment of swallowing disorders in elderly patients and those with stroke or tracheostomy has been widely reported (Rofes et al, 2011;Gandolfi et al, 2014;Garuti et al, 2014;Aoki et al, 2016), but no such studies have been reported for critically ill patients. Even in the ICU, evaluations of swallowing function and interventions by a multidisciplinary team should be performed to promote oral intake after extubation, and the effects of such evaluations and interventions should be verified.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, when considering dysphagia, interventions by a multidisciplinary team including doctors, nurses, SLPs, physical therapists, nutritionists and dental hygienists are necessary. The importance of multidisciplinary teams for the treatment of swallowing disorders in elderly patients and those with stroke or tracheostomy has been widely reported (Rofes et al, 2011;Gandolfi et al, 2014;Garuti et al, 2014;Aoki et al, 2016), but no such studies have been reported for critically ill patients. Even in the ICU, evaluations of swallowing function and interventions by a multidisciplinary team should be performed to promote oral intake after extubation, and the effects of such evaluations and interventions should be verified.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of abundant secretions and need for frequent tracheal aspirations in a 24-hour period are considered contraindications to decannulation (13,16) . It is worth emphasizing that cuff deflation favors better functionality of the larynx, thus allowing airflow through the upper airway, improved laryngeal elevation and sensitivity, removal of lung secretions, protection of the lower airways, voice, and deglutition.…”
Section: Discussionmentioning
confidence: 99%
“…The following criteria are suggested for indication and success in decannulation: ability to tolerate cuff deflation for 24h (9,10) ; presence of respiratory muscle strength and resistance (11,12) ; effective cough with ability to remove lung secretions (7,(9)(10)(11)(13)(14)(15) ; voluntary and reflexive cough (7,10,11,13) ; intact upper airways (5,9,13,15) ; absence of glottic or subglottic stenosis (16,17) ; preserved swallowing capacity (7,9,(11)(12)(13)(15)(16)(17) ; performance of the Blue Dye test (6,11,13,18) ; absence of previous head and neck surgery (7,11) ; use of phonation valve (11,14) ; tolerance to tracheostomy occlusion, with or without need for oxygen therapy (9,11,12,15,17) ; stable oxygen saturation for longer than 24h after tube occlusion (7,(9)(10)(11)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Il existe d'autre part un intérêt démontré à la gestion des patients trachéotomisés par une équipe spécialisée, de même qu'à la réalisation de protocoles guidant la décanulation [18][19][20] : diminution du nombre d'obstructions et de détresses respiratoires sur canule, diminution des complications liées à la décanulation, délai de décanulation raccourci avec augmentation du taux de succès, durée d'hospitalisation et dépenses de santé diminuées... Un tel suivi permet certainement une réévaluation plus fréquente des critères de décanu-lation et pourrait éviter de laisser en place des trachéotomies devenues inutiles. Cette équipe est multidisciplinaire et peut se composer de médecins réanimateurs ou tout médecin en charge du patient, d'ORL, d'orthophonistes, de kinésithéra-peutes, d'infirmières, formés à ce type de prise en charge.…”
Section: La Décanulation En Pratiqueunclassified